2007
DOI: 10.1089/clo.2006.0016
|View full text |Cite
|
Sign up to set email alerts
|

Development of Sheep Androgenetic Embryos Is Boosted following Transfer of Male Pronuclei into Androgenetic Hemizygotes

Abstract: Numerous studies have demonstrated the potential use of stem cells for the repair and regeneration of injured tissues. However, tracking transplanted stem cell fate and function in vivo remains problematic. To address these issues, murine embryonic stem (ES) cells were stably transduced with self-inactivating lentiviral vectors carrying either a triple fusion (TF) or double fusion (DF) reporter gene construct. The TF consisted of monomeric red fluorescence protein (mrfp), firefly luciferase (Fluc), and herpes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…5B) based on detecting phosphorylation and entrapment in the cells of the radiolabeled reporter probe [ 18 F]fluoro-hydroxymethylbutyl-guanine ([ 18 F]FHBG). The stability and efficiency of this reporter gene has been previously described (3). Imaging signals were stable from week 4 to week 8 after transplantation and correlated with the graft size measured by MRI analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5B) based on detecting phosphorylation and entrapment in the cells of the radiolabeled reporter probe [ 18 F]fluoro-hydroxymethylbutyl-guanine ([ 18 F]FHBG). The stability and efficiency of this reporter gene has been previously described (3). Imaging signals were stable from week 4 to week 8 after transplantation and correlated with the graft size measured by MRI analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the triple imaging modality, complexity of the model, and route of cell delivery, further studies are necessary to reconcile discrepancies with previous reports on the pattern of cell migration. We have previously used this vector to efficiently monitor pluripotent mouse embryonic stem cells for tumor formation after subcutaneous injections (3). The study demonstrated that HSV-ttk enables reliable noninvasive imaging and tracking of the marked increase in signal activity-associated subcutaneous tumor formation (3).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of investigations dealt with local administration of transduced cells followed by in vivo imaging of the gene product by bioluminescence, fluorescence, SPECT or PET scanning [36], [37], [38]. Tracking of intravenously administered transduced cells by nuclear medicine techniques is challenging and requires sensitive imaging modalities, stable transduction and use of radionuclide that will be optimal in respect to energy, half-life and cost.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al demonstrated the superiority of this technique compared to more standard 18 F-FDG and 18 F-Fluorothymidine ( 18 F-FLT) PET imaging for detecting teratoma formation following subcutaneous injection in mice (Cao et al, 2009). Alternatively, the PET reporter gene herpes simplex virus truncated thymidine kinase (HSV-ttk) can serve as both a monitor for tumor development and a suicide gene for ablative therapy (Cao et al, 2007a). Specifically, Cao et al transplanted mice with ESCs labeled with either a double-fusion (GFP and FLuc) or a triple-fusion construct (GFP, RLuc, and HSV-ttk).…”
Section: Defining Hurdles To Clinical Translation: Findings From Precmentioning
confidence: 99%